The Democratic Role of the National Library in Improving the Culture of Information Literacy During the Covid-19 Pandemic - Hari Otang Sasmita; Diah Amelia; Asima Sitanggang; Shinta Anggreany (2022)
This study was conducted to describe the role of the National Library (Perpustakaan Nasional) in improving literacy culture during the Covid-19 pandemic through the analysis of the SWOT+PEST communication strategy. With the desk research analysis method, data and information from observational information sources from online media and books combined with a description of the SWOT+PEST analysis, it was found that libraries can be said to play an important role in increasing public information literacy. The achievement of a strong literacy democracy can lead to a stronger development of Indonesia.